Policing and contemporary governance: the anthropology of police in practice - Garriott, William Campbell (Palgrave Macmillan, 2013)
What is it that police and policing actually do? What are the effects? How are these effects mediated and experienced by different people at different times and in different contexts? This volume draws attention to the centrality of police and policing to the project of governance and the experience of being human in the contemporary world